Análisis de las vulnerabilidades de las redes inalámbricas de RG Intelligent de la Parroquia La Unión, para mejorar la disponibilidad del servicio - Gaibor Manzo, Juan Carlos (2021)
This project aimed to analyze the vulnerabilities of RG INTELLIGENT wireless networks in the parish "La Union", in order to improve the availability of the service, in order to meet this objective applies or theories, methodology, methods and research instruments, technical visits were made to the entity to observe if the network equipment was installed correctly, it was found that the equipment was on an outdoor table exposed to dirt and handling of people outside the entity, also the cables were messy, the equipment was not connected to a voltage regulator or an ups and it could be seen that the equipment was lacking in maintenance as they had dust. The company is advised to purchase a voltage regulator or ups to avoid an inconvenience with electric power, also from time to time to maintain its network equipment, in addition a software called Nessus was used to analyze vulnerabilities of the company's network, a mid-level SMB Signing not required vulnerability was found, it poses no danger, to address this inconvenience you must enable the option to digitally sign communications in the local security policies of the server, this vulnerability is exploited by the SMB protocol, on port 445 of the server, commonly used to share files, printers, networks and other resources, it is concluded that the company if it has vulnerabilities which could be used by hackers or computer thieves in order to access the network, the respective recommendation was given to the owner of the business so that he is protected from any computer attack.